Bob Gordon (Robert Van Horn) and Frank Jones, 1958. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 4-14-58 p.1.
Bob Gordon (Robert Van Horn) and Frank Jones, 1958. Bob manned the television camera and Frank took photos for a visit by Dave Garroway and Wide Wide World Sunday to the Winston-Salem Journal newsroom.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth